Memorandum of understanding between Universiti Teknologi MARA and Universitas Jenderal Achmad Yani / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2019)
UiTM and Universitas Jenderal Achmad Yani endeavour to take necessary steps to encourage and promote cooperation.